2000
DOI: 10.1063/1.125698
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved photoluminescence studies of InxGa1−xAs1−yNy

Abstract: QzqiTime-resolved photolttminescence spectroscopy has been used to investigate carrier decay dynamics~t ifl> in a InXGa, -XASI.-,,NV (x-O.03, y -0.01) epilayer grown on GaAs by metal organic chemical vapor deposition. Time-resolved photohrmineseence (PL) measurements, performed for various 4%L excitation intensities and sample temperatures, indicate that the broad PL emission at low -gm temperature is dominated by localized exciton recombination. Lifetimes in the range of 0.07-0.34 a ns are measured; these pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
92
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(102 citation statements)
references
References 19 publications
9
92
0
1
Order By: Relevance
“…33,36,37 The degradation of PL efficiency at low N concentration in III-V semiconductor materials has been reported by several research groups. 12,42,43 Buyanova et al, for example, 43 observed similar nonradiative recombination channels, with activation energy of 50 meV, in the GaAsN/GaAs system. They suggested that these efficient competing nonradiative channels are located in the GaAsN layer, and that these channels are activated as soon as carriers are thermally detrapping from the localized states.…”
Section: Resultsmentioning
confidence: 80%
“…33,36,37 The degradation of PL efficiency at low N concentration in III-V semiconductor materials has been reported by several research groups. 12,42,43 Buyanova et al, for example, 43 observed similar nonradiative recombination channels, with activation energy of 50 meV, in the GaAsN/GaAs system. They suggested that these efficient competing nonradiative channels are located in the GaAsN layer, and that these channels are activated as soon as carriers are thermally detrapping from the localized states.…”
Section: Resultsmentioning
confidence: 80%
“…Important applications include lasers with wavelength in the 1.3-1.55 µm range, as well as solar cells with band gap around 1.0 eV [3]. Generally speaking the GaAsN and InGaAsN alloys have displayed evidence of inhomogeneities, such as broad photoluminescence (PL) line widths, variable PL decay times, and short minority carrier diffusion lengths [4][5][6][7]. Such observations are often taken as an indicator of compositional fluctuations in the materials, although direct structural characterization of such fluctuations is lacking.…”
mentioning
confidence: 99%
“…Consequently, the non-radiative transfer dominates on the high-energy side of the PL spectrum, which corresponds to all energies E > E m . The observed radiative transitions are either delocalized or slightly localized excitons, which can be easily transferred out of their sites 26 . Thus, they have extremely short decay times: e.g.…”
mentioning
confidence: 99%
“…The PL decay time of localized excitons decreases by a factor of 3.1 in a small energy interval of 14 meV. The energy dependent PL decay of localized excitons can be tted by 26,33 τ…”
mentioning
confidence: 99%
See 1 more Smart Citation